I feel retarded because i'm not getting this equation despite getting A's in all my math classes
\(i(t) = \frac{dq(t)}{dt}\)
some how becomes
\(q(t) = \int^{t}_{t_{0}} i(t)dt + q(t_{0})\)
I'm guessing we apply the integral operator \(\int dt\) to both sides. so where is the \(q(t_{0})\) coming from?
\(i(t) = \frac{dq(t)}{dt}\)
some how becomes
\(q(t) = \int^{t}_{t_{0}} i(t)dt + q(t_{0})\)
I'm guessing we apply the integral operator \(\int dt\) to both sides. so where is the \(q(t_{0})\) coming from?